2016
DOI: 10.1139/cjps-2015-0344
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide tank mixtures to control co-existing glyphosate-resistant Canada fleabane and giant ragweed in soybean

Abstract: Populations of glyphosate-resistant (GR) Canada fleabane and GR giant ragweed can be found in several locations in southwestern Ontario. While these species can be managed individually, a scenario has developed where both species are present in GR soybean. Ten separate field experiments (five with Canada fleabane and five with giant ragweed) were conducted over a 2-yr period (2013)(2014) in soybean to evaluate preplant (PP) herbicide tank mixtures that could control both weed species if they were present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Moreover, Hedges et al (2019) observed up to 10% soybean injury with the application of saflufenacil in different chemical management programs; however, the symptoms did not result in reduced soybean yield, thus demonstrating that the application of saflufenacil is effective in different management programs to control Conyza spp. (4,7,15,16,17,34). Other studies also demonstrated, as in the present study, the efficacy of flumioxazin in different combinations for the control of Conyza spp.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, Hedges et al (2019) observed up to 10% soybean injury with the application of saflufenacil in different chemical management programs; however, the symptoms did not result in reduced soybean yield, thus demonstrating that the application of saflufenacil is effective in different management programs to control Conyza spp. (4,7,15,16,17,34). Other studies also demonstrated, as in the present study, the efficacy of flumioxazin in different combinations for the control of Conyza spp.…”
Section: Discussionsupporting
confidence: 88%
“…Both 2,4-D and dicamba weed management programs have been found to be effective against Palmer amaranth, common waterhemp [ Amaranthus tuberculatus (Moq.) J. D. Sauer] (Cahoon et al 2015; Inman et al 2016; Meyer et al 2015), horseweed ( Erigeron canadensis L.) (Byker et al 2013; Flessner et al 2015; Ford et al 2014), and giant ragweed ( Ambrosia trifida L.) (Jhala et al 2014; Mahoney et al 2016), which are some of the most troublesome weedy pests in the United States (Van Wychen 2016).…”
mentioning
confidence: 99%
“…The application of glyphosate+saflufenacil has been reported effective especially to control eudicotyledon weeds, for example, Conyza spp. (Mahoney et al, 2016). However, saflufenacil does not present high control on Digitaria spp.…”
Section: Resultsmentioning
confidence: 96%